Peran Tenaga Kerja Perempuan Dalam Kegiatan Usahatani Jagung Di Desa Mopolo Kecamatan Ranoyapo Kabupaten Minahasa Selatan - Lumuko, Fajar Juandi; Pangemanan, Paulus Adrian; Manginsela, Elsje Pauline (Sam Ratulangi University, 2023)
The aim of this study is to know the role of women farmers in corn farming in Mopolo Village, Ranoyapo District, South Minahasa Regency. The study was conducted for 3 months from April 2022 to May 2022. Sampling used purposive sampling. This study uses primary data and secondary data. Primary data were obtained through direct interviews with female farmers who work in corn farming and are married. Interviews using a list of questions that have been prepared in the form of a questionnaire. Secondary data was obtained from the Mopolo Village office and other related references. The results of this study showed that the role of female workers that seen from women's working time in corn farming activities in Mopolo Village namely 106 hours for tillage activities, 44 hours for planting activities, 15 hours for weeding activities, 4 hours for pest and disease control, 32 hours for fertilizing activities and 89 hours for harvesting activies. The results of this study also indicate that female workers have less role in decision-making about planting activities, weeding activities, pest and disease control, fertilization activities, however those activities are dominated by men.